2009
DOI: 10.1590/s0102-76382009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia cardíaca videoassistida: resultados de um projeto pioneiro no Brasil

Abstract: Results: The surgical procedures were: plasty (n=20) or mitral valve replacement (n=36), aortic valve replacement (n=14), atrioseptoplasty using pericardial patch (n=32), tricuspid valve repair with rigid ring (n=6) and surgical correction of atrial fibrillation with radiofrequency (n=12). There were no complications during the procedures. There was no conversion to thoracotomy in neither case. Two patients developed atrial fibrillation in the postoperative period. There was an episode of stroke seven days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…In the group of congenital heart disease, those times were even lower, with 1.3 ± 0.5 days in ICU and 2.6 ± 0.8 days of postoperative hospitalization, numbers that demonstrate the expected result for this technique. Argenziano et al [41] reported 20 hours of admission and 4 days of hospitalization, Modi et al [40], six days of hospitalization, and Poffo et al [39], 6.5 days of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the group of congenital heart disease, those times were even lower, with 1.3 ± 0.5 days in ICU and 2.6 ± 0.8 days of postoperative hospitalization, numbers that demonstrate the expected result for this technique. Argenziano et al [41] reported 20 hours of admission and 4 days of hospitalization, Modi et al [40], six days of hospitalization, and Poffo et al [39], 6.5 days of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Only since 2005, with the beginning of our experience [16,37,38] and the experience of Poffo et al [39] in 2006, a new era of video-assisted cardiac surgery in our country has began, including intracardiac procedures via peripheral CPB, vacuum assist and minithoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Disposable pads for external cardiac defibrillation were placed in the region of the right scapula and anterolateral hemithorax. We performed the passage of nasopharyngeal thermometer and transesophageal transducer [2].…”
Section: Description Of Surgical Techniquementioning
confidence: 99%
“…The concern about the safety of direct aortic cannulation during surgery with smaller incisions was approached by Guedes et al [8], which demonstrated the method safety. Poffo et al [9] recently published their experience in this area, demonstrating a range of possible operations to be performed through a minimally invasive manner with peripheral cannulation, without complications due to cannulation and with good postoperative results. The same group demonstrated the possibility of performing the correction of associated heart diseases [10], as well as more complex techniques are also employed in minimally invasive manner [11].…”
mentioning
confidence: 99%